Housing Satisfaction and Aspirations of Householders in Salak Selatan Squatter Resettlement - Yahaya, Nurizan (1982)
A total of 163 householders in a squatter resettlemen t in Salak Selatan, Kuala Lumpur, were randomly selected and interviewed to assess their satisfaction and aspiration towards their houses. Most of the families (80%) had improved and enlarged the original units, as the City Hall had suggested, but the level of housing satisfaction was found to be moderate. Dissatisfaction was due to poorly designed floor plans, lack of space and specific types of rooms. The aspirations of the responden ts appeared to be realistic. Many of them indicated an awareness of the importance ofhaving more bedrooms as the size of the family increases. They found the single storey terrace housing suitable, but wanted additional types of rooms. Most of the respondents considered the area good for living and only a minority complained about environmental conditions. On the basis of the commen ts of the respondents suggestions are made for improving future housing projects.